Excess commuting : a critical review - Ma, K; Banister, D (Routledge, 2006)
Excess commuting is the additional journey-to-work travel represented by the difference between the actual average commute and the smallest possible average commute, given the spatial configuration of workplace and residential sites. Research on excess commuting has been carried out over the last 20 years since the seminal contribution of Hamilton (1982). The literature has generated much debate and controversy and the purpose of this review paper is to assess that material critically under three main headings: contextual, methodological and policy-related issues. The key contextual questions relate to the assumptions of transport optimization or cost minimization, socio-economic factors and how these are linked to urban spatial structure. The methodological issues cover spatial structure, aggregation, time or distance measures and the boundary problem, whilst the policy-oriented questions relate to the understanding of the effects of taking particular actions, including the behavioural response to policy initiatives.